The Exigency of Fossil Fuel Discontinuation for the Attainment of Indonesia’s Governmental Mandates in the Transition Towards Sustainable Energy - Annisa Permata Sari Harahap (JILPR Journal Indonesia Law and Policy Review, 2023)
This research discusses the urgency of addressing climate change, emphasizing the need to shift away from fossil fuels and transition to new and renewable energy sources. It highlights the increasing frequency of climate-related disasters and the global commitment to limiting temperature rise as outlined in the Paris Agreement. The text also mentions the challenges in Indonesia’s energy landscape, including a heavy reliance on fossil fuels and the importance of government intervention to promote renewable energy. It stresses the significance of a legal framework to support the transition to renewable energy and emphasizes the role of organizations like the Institute for Essential Services Reform (IESR) in driving this transition. Ultimately, it underscores the pressing need for decisive action to combat climate change and promote sustainable energy practices.